Aristotle’s Perceptual Realism in De anima III.1–2 - Corry, Patrick (Proceedings of the American Catholic Philosophical Association, 2023)
This paper argues that Aristotle in De anima is a direct realist about sense perception: the senses immediately perceive not only accidental qualities but independent beings. This thesis is supported primarily through an analysis of Aristotle’s condensed argument in DA III.1 that there can be no separate sense for common sensibles (such as number, shape, or motion). Against a more common reading of this passage, I argue that Aristotle intends to demonstrate that positing a separate sense for common sensibles entails a contradiction. This reconstruction of Aristotle’s argument in III.1 requires that Aristotle holds that the unity of simultaneous perception is grounded in the unity of objects perceived. I then show that this position helps us to understand the logical progression from DA III.1 to III.2, and to find in III.2 a theory of perception according to which perceptual activity is at once perception itself and the activity of the thing perceived. This principle grounds Aristotle’s position that the senses perceive things themselves directly.